Can we not just talk about men? the bechdel test, narrative salience and female voices in two selected Malay films - Jamaluddin Aziz,; Fuzirah Hashim,; Nor Fariza Mohd Nor, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Western feminist film scholars’ claim that female characters are often defined in relation to their male counterparts resonates well in contemporary film and gender studies. This claim highlights the representational biases towards male privilege and primacy as visible signifiers; the ramification of this biasness is the invisibility of female subjectivity that renders them voiceless. Therefore, inquiries into female subjectivity in films outside of Hollywood context are crucial. This paper aims at identifying and comparing the representation of female characters in two Malaysian films of two genres - romance and horror - to highlight the consonance between female voice with feminine consciousness and empowerment. This study administers the Bechdel Test on two films selected using criterion sampling - 3 Temujanji and Pontianak Harum Sundal Malam - and suggests a novel approach by adding the analysis of the film using the concept of narrative salience. The analyses using both methods revealed contradictory results. 3 Temujanji, although failed most of the test, is revealed through narrative salience as assiduous towards feminine consciousness and empowerment. Pontianak Harum Sundal Malam, which passed the test, ironically and ideologically contained female voices within the patriarchal value system. The finding contributes towards the theorisation that women's voices in Malaysian films can be considered as an integral part of the acoustic register of films that enhances film analysis technique. Scriptwriters and filmmakers can utilise the test as a reference in which women can define themselves 'not in relation to men', while creating female characters who progressively think beyond patriarchy and androcentrism.